(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2021)
Field studies were conducted in south and the High Plains of Texas as well as in southwestern Oklahoma during the 2014 and 2015 growing seasons to evaluate the effects of glyphosate plus dicamba combinations (1/16 X to 1 X of the 1.68 kg ae ha-1 rate) applied 30, 60, and 90 days after planting (DAP) on Spanish (Oklahoma) and runner (Texas) peanut. Rates were established to evaluate sub-labeled drift and direct application of a 1 X rate. Peanut stunting and death were more prevalent at the 30 and 60 DAP application while peanut were more tolerant of the 90 DAP application. In south Texas, peanut yields were reduced in both years when rates of ¼ X or greater were applied 30 and 90 DAP while rates of 1/8 X or greater reduced yield when applied 60 DAP. At the High Plains location, peanut yields were consistently reduced with rates of ½ X or greater applied 30 and 90 DAP and ¼ X or greater applied 60 DAP. In Oklahoma, peanut yield were consistently reduced with rates of ¼ X or greater applied 30 and 60 DAP and 1/16 X or greater when applied 90 DAP. Peanut grade was more affected by the 60 and 90 DAP application than the 30 DAP application.